Potential use of Pennisetum purpureum for phytoremediation of arsenic in treatment sand: a phytotoxicity study - Rahman, Md Ekhlasur; Uddin, Md Kamal; Shamsuzzaman, S.M.; Mahmud, Khairil; Abd Shukor, Mohd Yunus; Abd Ghani, Siti Salwa; Nabayi, Abba; Sadeq, Buraq Musa; Chompa, Sayma Serine; Akter, Amaily; Halmi, Mohd Izuan Effendi (Elsevier, 2024)
Using Pennisetum purpureum for phytoremediation is a promising technology for vigorous along with deep root systems and producing large amounts of biomass while remediating contaminated soil. The objective of the current investigation was to assess the highest level of As(V) that the plants can tolerate, to identify the toxicity symptom of As(V) on plants, and how much amount of As(V) that plants can uptake during the phytoremediation operation. In this investigation, phytotoxicity and phytoremediation by P. purpureum were evaluated at 0, 5, 20, 40, 60, and 80 mg As(V) kg−1 sand for 28 days. The total extractable and bioavailable As(V) were analyzed utilizing the wet digestion and Na2-EDTA method respectively and both the As(V) were determined by ICP-OES. P. purpureum can tolerate up to 40 mg As(V) kg−1 sand however the plant wilted and dried at 60 and 80 mg As(V) kg−1 sand. As(V)-induced phytotoxicity signs increased with rising As(V) levels in the treated sand and days of treatment. In the case of 60 and 80 mg As(V) kg−1 sand, P. purpureum withering started from the 3rd and 2nd day of transplanting in As(V) contaminated sand and on the 7th and 5th day the plants were completely withered respectively. P. purpureum plants could uptake the highest As(V) of 1549.26 ± 41.83 mg kg−1 DW for 40 mg As(V) kg−1 sand on 28 days trial. These results suggest that P. purpureum can be used for As phytoremediation in agriculturally and anthropogenically polluted environments due to its high uptake and bioaccumulate of As(V).